Geochemical and Limnological Characterization of the Corta Atalaya Pit Lake (Riotinto Mines, Spain) - Esther Santofimia; Blanca Rincón-Tomás; Enrique López-Pamo; Francisco Javier González; Ricardo Amils (Materials Proceedings, 2023)
This study examines some relevant limnological and hydrogeochemical characteristics of the most emblematic pit lake of the Iberian Pyrite Belt (IPB). Corta Atalaya (CA) open pit mine is known for its large size and for being one of the most important exploitations of copper in Europe. Despite its historical importance, little is known about the lake formed in this open pit. During this study, the pit lake presented a surface area of 16 ha, a maximum depth of 106 m, and a 5.8 hm3 volume of acid and metal-enriched water. CA pit lake shows permanent chemical stratification (meromictic lake), where three layers with different density and chemical composition can be differentiated: (i) a superficial layer of 5 ± 2 m water depth, with electric conductivity (EC) between 5.4–6.64 mS/cm, and oxygenated and Fe(III)-rich mixolimnion; (ii) an intermediate layer (between 5–30 m, chemocline), exhibiting strong vertical changes in parameters such as temperature (T) and EC, which show an increase with depth; and (iii) a thick bottom layer from 30 m to 106 m depth, with anoxic, elevated EC (47 mS/cm) and T (32 °C) values, and a concentration of Fe as Fe(II) (monimolimnion).The characterization of the water column is essential to know the potential sources of strategic and critical raw materials, and to evaluate their possible recuperation, thereby activating a circular economy.